Descentralização e formulação de políticas de saúde: um estudo da capacidade institucional administrativa em um município de médio porte do sul de Minas Gerais - Gomes, Marília Della Lucia (2016)
The decentralization process established by the Constitution of 1988, as well as the recognition of the autonomy of the municipalities, being a specificity of Brazilian federalism, were designed to ensure local empowerment. In recent years, a reconversion in the discussion concerning the role of a State, especially in the field of centralization and decentralization, was noticed. The Federal Government, has sought to promote greater coordination/formulation of public policies, delegating the role of implementers to the municipalities, by means of establishing central social policies, among which are health policies. In this scenario, health policies developed within the Unified Health System (SUS) are important objects of analysis concerning the process of administrative decentralization in Brazilian federalism, especially considering the formulation and coordination exercised by the Union and the eminent implementing activity of the States, and especially municipalities. This paper is a case study in a medium-size southern municipality of Minas Gerais (MG), Brazil, aimed at evaluating the capacity of the municipality in formulating health policies. Therefore, the study evaluates the state's capacity to formulate health policy-making in the municipality of Lavras - MG, based on institutional and administrative dimensions. To this end, we identified the main health policies formulated between January 2011 and June 2015. Based on this empirical research, and in order to analyze if the identified policies stem from the local policy-making activity or from the implementation of policies defined by the Federal Government, we reserved a discussion topic of the collected data opposing the theoretical perspectives presented. Based on the analyzes of the federal configuration of health policies, we proposed to redesign the cycle of public policies within the Brazilian Federative State.